Pengaruh Pembebanan RLC Terhadap Stabilitas Daya Semu dan Kinerja Sistem Pembangkit Listrik Tenaga Bayu (PLTB) - Mas Ahmad Baihaqi; Abdillah, Hartawan; Winda Ayu Mundari; Asrori, Tamam; Muhammad, Alief; Prasetiyo, Dani Hari Tunggal; Agung Fitrahadi (Journal Electric Field, 2025)
This study aims to evaluate the impact of RLC loading on the power stability and power quality in Wind Power Plant (PLTB) systems. The RLC is applied to stabilize the power generated by the PLTB system, which tends to fluctuate due to wind speed variability. The testing was conducted by measuring the output power of the PLTB system loaded with various RLC configurations. The results show that RLC loading can enhance the apparent power stability and efficiency of the PLTB system. The resistive load (R) yielded the best performance, improving the power factor to 0.95 and maintaining relatively stable output voltage. Meanwhile, the LC loads exhibited lower efficiency with a reduced power factor, but still played a role in balancing reactive power. The reduction in reactive power for inductive and capacitive loads indicates that RLC loading can help reduce power waste and improve power quality. This research makes a significant contribution to the development of more efficient and stable PLTB systems and more reliable renewable energy-based power plants, particularly in managing power stability in the face of fluctuations caused by wind variability.